Lynching in Colorado, 1859-1919 - Leonard, Stephen J., editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2002)
In this examination of more than 175 lynchings, Stephen J. Leonard illustrates the role economics, migration, race, and gender played in the shaping of justice and injustice in Colorado. One of the first comprehensive studies of the phenomenon in a Western state, Lynching in Colorado provides an essential complement to recent studies of Southern lynchings, demonstrating that at times the land of purple mountain's majesty was just as lynching-prone as was the land of Dixie. Written for general fans of Western history as well as scholars of American culture, Lynchings in Colorado shows Westerners at their worst and their best as they struggled to define law and order.--Provided by publisher.
People's courts and vigilance committees, 1859-1861 -- Major towns, 1860s-1880s -- The hinterland -- The Cuddigan and other lynchings, 1884-1906 -- Tug-of-war -- Race and lynching.
Keywords: Lynching -- Colorado -- History -- 19th century